Cenozoic rifting, passive margin development and strike-slip faulting in the Andaman Sea: A discussion of established v. New tectonic models - C. K. Morley (2018)
© 2017 The Author(s). Published by The Geological Society of London. The Andaman Sea evolved from near-pure extension (WNW-ESE) during the Late Palaeogene, to highly oblique extension (NNW-SSE) during the Neogene, to strike-slip-dominated deformation (Late Miocene-Recent). These changes in extension direction and deformation style probably reflect the switch from slab rollback-driven extension to India coupling with Myanmar and driving oblique extension/dextral strike-slip. The East Andaman, Mergui-North Sumatra and Martaban Shelf basins, along with the Alcock and Sewell rises and Central Andaman Basin (CAB), were all involved with this deformation which became increasingly focused on the CAB and the rises with time. Possible revisions to traditional models for the Andaman Sea include: (1) the Alcock and Sewell rises are hyper-extended continental or island arc crust, not Miocene oceanic crust; (2) the East Andaman Basin is predominantly underlain by strongly necked to hyper-extended continental crust, not oceanic crust; or (3) CAB oceanic crustis ofMiocene, not Pliocene-Recent age. Atpresentanumber of majorissues can be addressed but not fully resolved, including: (1) the distribution, timing, volume and origin of magmatism in the basins; (2) the causes and significance of strong crustal reflections imaged on 2D and 3D seismic data; (3) implications for crustal thinning geometries, upper crustal extensional patterns and distribution of igneous intrusions for current models of passive margin development (i.e. volcanic v. Non-volcanic margins), and how the back-arc setting modifies these models. Elements of both volcanic and non-volcanic margins are present in the East Andaman Sea, with well-developed necking of continental crust (perhaps due to dry mafic, granulite facies lower crust) and extensive igneous intrusions in the lower and middle crust.